The Influence of Brand Image, Brand Trust, and Digital Marketing on Consumer Purchase Decisions at Nibra’s House Kraksaan - Deva Ummu Azizah; Muh Hamzah (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to analyze the influence of brand image, brand trust, and digital marketing on consumer purchase decisions at Nibra's House Kraksaan. Research Method: This study employed a quantitative approach using primary data collected through questionnaires distributed to consumers of Nibra's House Kraksaan. The population comprised 3,200 consumers, and 355 respondents were selected through purposive sampling. Data were analyzed using multiple linear regression in SPSS. Results and Discussion: The findings indicate that brand image, brand trust, and digital marketing have positive and significant effects on consumer purchase decisions, both partially and simultaneously. Brand trust demonstrated the strongest influence among the independent variables. The coefficient of determination indicates that brand image, brand trust, and digital marketing jointly explain 41.3% of the variance in consumer purchase decisions, with the remaining 58.7% attributable to other factors beyond the scope of this study. Implications: The results suggest that companies should strengthen their brand image, maintain consumer trust, and optimize their digital marketing strategies to influence consumer purchase decisions. Originality: This study contributes to the marketing literature by examining the combined effects of brand image, brand trust, and digital marketing on consumer purchase decisions in the context of a local Muslim fashion retailer, namely Nibra’s House Kraksaan, an area that has received limited empirical attention in previous studies.